Determinants of households' participation in tree planting activities at the REDD+ project sites in Southern Leyte, Philippines - Armenia, Pedro T.; Castillo, Glorybeth C. (2015)
This paper aims to identify the determinants of households' participation in tree planting activities using available survey data, which included 797 randomly selected smallholder households from five REDD+ Pilot project sites in Southern Leyte, Philippines. Binary logit regression model was employed to identify the factors that affected household-respondents' decisions to participate in tree planting or tree farming activities. The model was also employed to predict the probability of participation for given socio-economic and other characteristics of smallholder households. Results of the analysis show that REDD+project site, membership in an organization, experience in environmental risks, access to natural resources, household size, and the total on-farm income of households were positively associated with tree planting. On the other hand, non-farm income, age of spouse and decisions on production and livelihood activities that were made solely by household heads were negatively associated with participation. These determinant factors, in conjunction with their associative influence on participation, may be used as inputs for instituting or redesigning a roadmap aimed at enhancing smallholders' participation in tree planting activities and ventures.
Keywords: Tree planting